Influência da temperatura e período de armazenamento na composição química e fisico-química de frutos de abacaxi da cv. Pérola - Zorzal, Tatiane Aparecida (2015)
The use of temperature for the storage of fruits for conservation of acceptable characteristics to market and increase the shelf life is a simple procedure, because it reduces the metabolism fruits besides delayed ripening process. Therefore, the aim of this work was to check the physical and physico-chemical changes in pineapple fruits subjected to storage at different temperatures. Fruits of pineapple cv. Pérola selected in the Central de Abastecimento do Espírito Santo, Espírito Santo, Brazil, were subjected to differents temperatures at 4°, 8°, 12°, 16° e 22° for 23 days. The analysis performed in the intervals of 4, 8, 16 and 23 days, included: soluble solids, pulp pH, titratable acidity, reason soluble solids/titratable acidity, phenolics compounds, antioxidant capacity, as well as, the enzimes peroxidase, polyphenoloxidase, phenylalanine ammonia-lyase and catalase. The results showed that the temperatures of 16° and 22° C are not recommended for storage of fruits, such as temperatures were not sufficient to prevent the ripening of fruits, as well as the appearance of diseases such as fusariosis and a black rot. However, fruits storage in the temperatures (4°, 8° and 12° C) even long periods maintained characteristics accepted for consumption, which increases the shelf life of fruits. The storage temperature to 12° C, stood out as great, allowing maintain the best quality of the fruit, requiring a lower cost for maintenance the storage incubators